2009
DOI: 10.1080/03091900802451232
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of semi-automated method for femur length measurement from foetal ultrasound

Abstract: The motivation of this paper is to analyse the efficiency and reliability of our proposed algorithm of femur length (FL) measurement for the estimation of gestational age. The automated methods are divided into the following components: threshold, segmentation and extraction. Each component is examined, and improvements are made with the objective of finding the optimal result for FL measurement. The methods are tested with a total of 200 different digitized ultrasound images from our database collection. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Previous studies demonstrated the feasibility of automated fetal biometric measurements 1,7-13 and that this approach is both reliable and reproducible. 13 More recently, Zalud et al 1 demonstrated that automated measurements of the biparietal diameter, head circumference, abdominal circumference, and femur length were comparable to the manual measurements done by sonographers. An accumulating body of evidence indicates the feasibility of automatic fetal biometric measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies demonstrated the feasibility of automated fetal biometric measurements 1,7-13 and that this approach is both reliable and reproducible. 13 More recently, Zalud et al 1 demonstrated that automated measurements of the biparietal diameter, head circumference, abdominal circumference, and femur length were comparable to the manual measurements done by sonographers. An accumulating body of evidence indicates the feasibility of automatic fetal biometric measurements.…”
Section: Discussionmentioning
confidence: 93%
“…Rahmatullah et al ,. using semi‐automated measurement of the femur after segmentation and extraction, and Zalud et al ,.…”
Section: Discussionmentioning
confidence: 99%
“…7 Subsequently, other groups provided additional evidence for the feasibility of automated measurements of the biparietal diameter and head circumference, 9,10 abdominal circumference and head circumference, 12 as well as femur length. 13 More recently, Zalud et al 1 demonstrated that automated measurements of the biparietal diameter, head circumference, abdominal circumference, and femur length were comparable to the manual measurements done by sonographers. Moreover, the authors indicated good interobserver variability with the use of the automated method.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, automatic fetal biome- try may improve the efficiency of prenatal sonography. Previous studies demonstrated the feasibility of automated fetal biometric measurements 1,[7][8][9][10][11][12][13] and that this approach is both reliable and reproducible. 1 However, our study further demonstrates that the automatic biometric method is more efficient than the manual one in the setting of a busy ultrasound practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation